Pathways to resilient dryland food systems in Africa: Strategic and tactical choices for accelerated impacts - Marenya, Paswel P.; Narmandakh, Davaatseren; Kirui, Leonard; Odhong, Jonathan A.; Sanni Abdulrahman; Aboudoulaye, Soule B.; Adam, Mamadou; Alex, Gerald; Belko, Marème N.; Bett, Charles; Dembele, Bandiougou; Derik, Sakatali P.; et al. (International Maize and Wheat Improvement Center, 2024)
Africa’s drylands form vital food systems, supporting a significant portion of its population and agricultural activity. However, they face persistent challenges with low productivity, limited market integration, and acute vulnerability to climate shocks. These issues contribute to structural poverty and high rates of undernourishment, highlighting the need for investments to improve rural incomes, enhance resilience, and foster economic growth.